An Evaluation of Lubricating Properties of CuO and h-Boron Nitride (h-BN) - K. Gocman; T. J. Kaldonski; T. Kaldonski; Z. Pawlak (Tribology Online, 2020)
The purpose of this paper is to study the tribiological behavior of (steel/porous iron), (steel/steel) and (steel/bronze) tribopair with micellar copper oxide, hexagonal boron nitride (h-BN), Lithium grease Liten LT43 and base oil, transformer mineral oil, and mineral oil SN650 as lubricants. The results are discussed in the form of performance such as wear surface, friction coefficient, weld point, limiting load wear and load-carrying capacity. It is found that (steel/bronze) friction pair contacts develop into a (copper/copper) contact along the sliding time. Worn surfaces were examined using XPS to determine the friction mechanism. The lower friction by additives is based on the formation of metallic copper tribofilm, and lamellar h-BN lubrication mechanism is discussed.